Effect of nano graphene and CNT addition on coating properties in friction surfacing process - Erdem, Serkan (Walter de Gruyter Gmbh, 2022)
In this study, the wear behaviour of the composite material obtained as a result of the coating process by adding nano-size powder to the consumable rod with the friction surfacing method was investigated. An amount of 3-5 wt% nano graphene and carbon nano tube (CNT) were added into the hole drilled at a certain depth in the center of the consumable rod, and then the rod was subjected to sintering process. The obtained consumable rod was deposited on the substrate material at a certain rotational speed, horizontal and vertical progression speeds by friction surfacing method. Wear tests were carried out by subjecting the deposited surface samples to the pin-on-disc wear test. According to the results obtained, the increase in the additive ratio decreased the wear rate by approximately 30% in the 3 wt% graphene additive sample and 75% in the 5 wt% additive sample for 900 m wear distance. The same CNT additive ratios decreased the wear rate in the sample by 41% and 58%, respectively.
Keywords: CNT; coating; friction surfacing; graphene; tribology; wear